(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
According to the announcement of LIGO, it is exciting that the gravitational wave has been confirmed,. Perhaps, this is the time for physicists to fix the Einstein equation for the gravitational wave and the nonexistence of the dynamic solution. These two problems are inextricably related. As a first step, theorists should improve their pure mathematics beyond Einstein on non-linear mathematics and related physical considerations. Then, it is time to rectify the Einstein equation that has no gravitational wave solution which Einstein has recognized, and no dynamic solution that Einstein failed to see. Moreover, in view of the far distance of the sources, it is very questionable that one can determine they are black holes, which actually also have no theoretical basis.